Investigations into human influenza transmission - Killingley, Ben (2013)
Limited understanding of influenza transmission has been a frequent obstacle during the development of pandemic influenza infection prevention and mitigation strategies. The science is hotly debated, especially the relative importance of transmission via large droplets or aerosols. Clarification of the relative importance of different modes of transmission is critical for the refinement of evidence-based infection control advice and has been called for by the European Center for Disease Control (ECDC), the World Health Organization (WHO), and the US Institute of Medicine.